Teknik Searching and Gathering (Segath) untuk Meningkatkan Hasil Belajar Al-Qur’an Hadist Pada Mapel PAI dan Budi Pekerti - Erfina Zulayda Anis (Balai Diklat Keagamaan Semarang, 2023)
Al-Qur'an Hadith material is one of the aspects in the Subject of Islamic Religious Education and Morals. The purpose of this study was to find the right technique to make students understand more about the Al-Qur'an Hadith material, namely Surat Attin and improve learning outcomes. Segath stands for Searching and Gathering which means searching and gathering. The research method that the writer did in this study was a qualitative-descriptive research method. The research target is class 5A students in semester 1 of the 2022/2023 school year. The initial data that the writer took was the value of the daily assessment results of the Al-Qur'an Hadith before using the Segath Technique and the value of the results of the daily assessment after using the Segath Technique. The author also made observations through observation sheets to observe an increase in student motivation while participating in Al-Qur'an Hadith learning with the Segath Technique. This segath technique is applied by the author to the Qur'anic material in Attin's letter. Segath combines independent learning activities via the internet, creative writing and physical activity. Students actively seek knowledge about letter material from the internet (searching) then share knowledge with their friends in a fun activity (gathering). The Segath technique helps students memorize and understand the meaning contained in Attin's letter, as evidenced by the increase in the average learning outcomes to 86.6 with the highest score of 95 and the lowest score of 80, from the previous average of 75.88 with a maximum score of 90 and a minimum of 40. Learning motivation also increases and learning is more interesting.